2000
DOI: 10.1128/aac.44.10.2919-2921.2000
|View full text |Cite
|
Sign up to set email alerts
|

Bactericidal Activities of HMR 3647, Moxifloxacin, and Rifapentine against Mycobacterium leprae in Mice

Abstract: Bactericidal activities of HMR 3647 (HMR), moxifloxacin (MXFX), and rifapentine (RPT) againstMycobacterium leprae, measured by the proportional bactericidal technique in the mouse footpad system, were compared with those of the established antileprosy drugs clarithromycin (CLARI), ofloxacin (OFLO), and rifampin (RMP). Administered in five daily doses of 100 mg/kg of body weight, HMR appeared slightly more bactericidal than CLARI. In a single dose, MXFX at 150 mg/kg was more active than the same dose of OFLO an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…The ranking of the activities of these quinolones based on the inhibition of DNA supercoiling and the induction of DNA cleavage was similar to that based on the activities against M. leprae in the mouse footpad system or in in vitro assays (Table 1). For example, moxifloxacin is highly active at inhibiting M. leprae DNA gyrase and is also by far the most active quinolone against M. leprae in the mouse footpad system (8); on the other hand, ofloxacin is less active at inhibiting the DNA gyrase and is also significantly less bactericidal than moxifloxacin in the mouse (8). Despite good in vitro activity against the purified enzyme, ciprofloxacin is poorly active in vivo, probably due to unfavorable pharmacokinetics (15) and the lack of an intracellular killing ability (30).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…The ranking of the activities of these quinolones based on the inhibition of DNA supercoiling and the induction of DNA cleavage was similar to that based on the activities against M. leprae in the mouse footpad system or in in vitro assays (Table 1). For example, moxifloxacin is highly active at inhibiting M. leprae DNA gyrase and is also by far the most active quinolone against M. leprae in the mouse footpad system (8); on the other hand, ofloxacin is less active at inhibiting the DNA gyrase and is also significantly less bactericidal than moxifloxacin in the mouse (8). Despite good in vitro activity against the purified enzyme, ciprofloxacin is poorly active in vivo, probably due to unfavorable pharmacokinetics (15) and the lack of an intracellular killing ability (30).…”
Section: Figmentioning
confidence: 99%
“…Within the last 20 years, a number of newer antimicrobial agents, such as the quinolones (e.g., pefloxacin, ofloxacin, sparfloxacin, and moxifloxacin), the macrolides (e.g., clarithromycin), and the tetracyclines (e.g., minocycline), that possess various degrees of bactericidal activity against M. leprae have been identified in mouse experiments and in human trials (18,19). Among these newer antimicrobial agents, moxifloxacin has been demonstrated to display very powerful bactericidal activity against M. leprae (8) that is virtually identical to that of rifampin (the key component of the current MDT regimens) and has been well tolerated in human trials (26). Therefore, moxifloxacin may become an important component of a future MDT regimen.…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that both moxifloxacin (MXF), a newer fluoroquinolone, and R207910, a diarylquinoline, exhibit powerful bactericidal activity against M. tuberculosis (2,14) and M. leprae (7,15) (3,9,10).…”
mentioning
confidence: 99%
“…In animal experiments, moxifloxacin is highly active against M. leprae, in particular in combination with rifapentine/minocycline [206].…”
Section: Skin Infectionsmentioning
confidence: 99%